The Crossregulation Triggered by Bacillus Strains Is Strain-Specific and Improves Adaptation to Biotic and Abiotic Stress in Arabidopsis - Estrella Galicia-Campos; Ana García-Villaraco Velasco; Jose Antonio Lucas; F. Javier Gutiérrez-Mañero; Beatriz Ramos-Solano (Plants)
Plants are sessile organisms that overcome environmental stress by activating specific metabolic pathways, leading to adaptation and survival. In addition, they recruit beneficial bacterial strains to further improve their performance. As plant-growth-promoting rhizobacteria (PGPR) are able to trigger multiple targets to improve plant fitness, finding effective isolates for this purpose is of paramount importance. This metabolic activation involves the following two stages: the priming pre-challenge with no evident changes, and the post-challenge, which is characterized by a faster and more intense response. Eight Bacillus strains, obtained in a previous study, were tested for their ability to improve plant growth, and to protect Arabidopsis thaliana plants against biotic and abiotic stress. After the 16S rRNA gene sequencing, three isolates were selected for their ability to improve growth (G7), and to protect against biotic and abiotic stress (H47, mild protection, with a similar intensity for biotic and abiotic stress; L44, the highest protection to both); moreover the expression of Non-Expresser of Protein Resistance Gene 1 (NPR1) and Protein resistance (PR1) as markers of the Salicylic Acid (SA) pathway, and lipooxygenase (LOX2) and plant defensin gene (PDF1) as markers of the Ethylene/Jasmonic Acid (Et/Ja) pathway, was determined 24 h after the stress challenge and compared to the expression in non-stressed plants. The results indicated that (i) the three strains prime Arabidopsis according to the more marked and faster increases in gene expression upon stress challenge, (ii) all three strains activate the SA-mediated and the Et/Ja-mediated pathways, therefore conferring a wide protection against stress, and (iii) PR1 and PDF1, traditionally associated to Systemic Acquired Resistance (SAR) and Induced Systemic Resistance (ISR) protection against pathogenic stress, are also overexpressed under abiotic stress conditions. Therefore, it appears that the priming of the plant adaptive metabolism is strain-dependent, although each stress factor determines the intensity in the response of the expression of each gene; hence, the response is determined by the following three factors: the PGPR, the plant, and the stress factor.